Clinical differences between Raoultella spp. and Klebsiella oxytoca - Mettler, Sofia K.; Charoenngam, Nipith; Colgrove, Robert C. (Frontiers in Cellular and Infection Microbiology, 2024)
Purpose: Raoultella spp. is a genus of bacteria that is known to be closely related to Klebsiella. It has been debated whether Raoultella should be reclassified as a subgroup of Klebsiella. The aim of this study is to compare clinical aspects of Raoultella and Klebsiella oxytoca, a species of Klebsiella that is known to be bacteriologically similar to Raoultella spp. Methods: Using data collected at a tertiary care hospital in the United States, we identified 43 patients with Raoultella infection and 1173 patients with Klebsiella oxytoca infection. We compared patient demographics (age and sex), hospitalization status, isolation sites and antibiotic resistance profiles between the two species. Results: There was no significant difference in patient demographics between the two bacteria species. The proportions of intensive care unit (ICU) admission was higher among patients with Raoultella infection (p=0.008). The most common site of isolation was urine for both species (39.5% of all patients with Raoultella spp. vs. 59.3% for K. oxytoca). The second most common site of isolation was blood stream for Raoultella spp. (23.3%) and respiratory tract for K. oxytoca (10.8%). Except for the high proportion of resistant isolates of Raoultella spp. for Trimethoprim/sulfamethoxazole, the antibiotic susceptibility profiles were similar between the two bacteria species. Both were susceptible to ciprofloxacin and meropenem. Conclusion: While there are no significant differences in the patient demographics and antibiotic susceptibility profiles between Raoultella spp. and K. oxytoca, Raoultella may cause more serious infection requiring ICU admissions. Also, Raoultella may cause blood stream infection more frequently than K. oxytoca.